2015
DOI: 10.1515/cclm-2014-0598
|View full text |Cite
|
Sign up to set email alerts
|

Erroneous HbA1c measurements in the presence of β-thalassemia and common Chinese hemoglobin variants

Abstract: β-Thalassemia can cause errors in HbA1c determination using the Variant II Turbo system. HbE heterozygosity or HbE homozygosity also complicated HbA1c measurements. The Capillarys 2 Flex Piercing system detected all Hb variants and HbA1c in patients with β-thalassemia and could provide measurements with high accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…However, this does not mean that all issues related to this subject have been addressed. For example, Ji et al demonstrate here that β-thalassemia can still lead to misinterpreting HbA 1c results, and highlight the importance of the optimal characterization and knowledge of every method with respect to interferences [17]. Moreover, less common variants may induce unexpected interferences with different impacts on the methods, as recently demonstrated elsewhere by Little et al [18].…”
supporting
confidence: 57%
“…However, this does not mean that all issues related to this subject have been addressed. For example, Ji et al demonstrate here that β-thalassemia can still lead to misinterpreting HbA 1c results, and highlight the importance of the optimal characterization and knowledge of every method with respect to interferences [17]. Moreover, less common variants may induce unexpected interferences with different impacts on the methods, as recently demonstrated elsewhere by Little et al [18].…”
supporting
confidence: 57%
“…However, Tosoh HLC‐723 G8 analyzer could not detect some rare hemoglobin variants such as Hb J‐Baltimore in HbA1c mode 4 . Ji et al showed that heterozygous Hb E or homozygous Hb E might affect the detection of HbA1c by HPLC depending upon the specific assay machine 5 . Therefore, in the detection of HbA1c, the recognition of hemoglobin variants is very necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal β chain hemoglobin in southern areas are mainly HbE, Hb Newyork, and Hb J-Bangkok, the Hb variants prevalent in northern China include HbG Taipei and HbD Punjab. [20] Previous studies have shown that the presence of Hb variants such as HbS, HbD, or HbE interfered with HbA1c measurement results with some methods [21], but few studies have examined the potential interference from Hb J-Bangkok. Hb Newyork, and HbG Taipei on HbA1c measurements.…”
Section: Discussionmentioning
confidence: 99%